2021
DOI: 10.1016/j.mayocp.2020.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Thrombotic Events in Adult Inpatients With COVID-19

Abstract: Objective: To evaluate the clinical course of and risk factors for arterial thrombotic events in adult inpatients with coronavirus disease 2019 . Methods: All consecutive adult patients admitted for COVID-19 infection in a referral center in France and discharged from the hospital between April 1 and April 30, 2020, were included. All arterial thrombotic events that occurred through discharge were considered for analysis. Epidemiologic, demographic, clinical, laboratory, treatment, and outcome data were extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 23 publications
2
47
0
1
Order By: Relevance
“…In one large retrospective observational study of 3556 patients, 32 (0.9%) developed an ischaemic stroke, 4 occurring without any symptoms of COVID-19 prior to the event, and in the remainder of cases, stroke developed up to 27 days following COVID-19 symptom onset [14]. Two further reports of COVID-19 in hospital have identified an incidence of arterial thrombosis in 1.8% of 2021 patients, and 5.6% of 531 patients [15,16].…”
Section: Thrombotic Complications Of Covid-19 Amongst Hospitalised Patientsmentioning
confidence: 99%
“…In one large retrospective observational study of 3556 patients, 32 (0.9%) developed an ischaemic stroke, 4 occurring without any symptoms of COVID-19 prior to the event, and in the remainder of cases, stroke developed up to 27 days following COVID-19 symptom onset [14]. Two further reports of COVID-19 in hospital have identified an incidence of arterial thrombosis in 1.8% of 2021 patients, and 5.6% of 531 patients [15,16].…”
Section: Thrombotic Complications Of Covid-19 Amongst Hospitalised Patientsmentioning
confidence: 99%
“…24 Although ALI is a complication of COVID-19 in hospitalized patients, it is now being understood that it can arise in patients with mild COVID-19 symptoms, and that ALI can be the first presenting sign of COVID-19 even in the absence of respiratory symptoms. 27 In a study of 49 patients diagnosed with COVID-19, 22 (45%) showed symptoms of acute arterial ischemia before being diagnosed with COVID-19, while the remaining 27 (55%) experienced ischemia during hospitalization. 28 Infected patients with little to no COVID-19 symptoms can experience a prothrombotic state, and some studies have identified patients who complained mostly of acute extremity discomfort, which was mostly accompanied by moderate respiratory symptoms or other COVID-19 symptoms, although in some instances, ALI was the only clinical manifestation of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Another mechanism is the inflammatory storm through secretion of mediators, such as interleukin-6 (IL-6), and production of C-reactive protein (CRP), fibrinogen, ferritin, and D-dimer, which triggers the complement cascade, thus inducing a hypercoagulable state [ 7 ]. All these mechanisms have been linked to the degree of COVID-19 severity [ 17 ]. Additionally, autoantibodies, such as antiphospholipid and anticardiolipin, have been described in sporadic cases of COVID-19; another theory to explain hypercoagulability is related to the neutrophil extracellular traps that are formed to contain the virus within vessels, which have been associated with triggering of the intrinsic coagulation pathway [ 18 ].…”
Section: Discussionmentioning
confidence: 99%